2013
DOI: 10.1080/15475441.2013.849176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parental Interaction on Infant Vocalization Rate, Variability and Vocal Type

Abstract: Examination of infant vocalization patterns across interactive and noninteractive contexts may facilitate better understanding of early communication development. In the current study, with 24 infant-parent dyads, infant volubility increased significantly when parent interaction ceased (presenting a “still face,” or SF) after a period of normal interaction (“face-to-face,” or FF). Infant volubility continued at the higher rate than in FF when the parent re-engaged (“reunion,” or RE). Additionally, during SF, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 64 publications
2
58
1
1
Order By: Relevance
“…Keller & Schőlmerich, 1987; Goldstein et al, 2003) have tended to show the circumstance in which parents contingently talk to their infants to be the most conducive context for the production of vocalisations, and still-face studies (e.g. Goldstein et al, 2009; Franklin et al, 2014) have reported that a context when the primary caregiver withdraws after interaction to not talking or interacting with the infant elicits high rates of vocalisations from infants at least 5 months of age. Note, however, that in these lines of research, interaction and effects of increased interaction or withdrawal from it have been the exclusive focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keller & Schőlmerich, 1987; Goldstein et al, 2003) have tended to show the circumstance in which parents contingently talk to their infants to be the most conducive context for the production of vocalisations, and still-face studies (e.g. Goldstein et al, 2009; Franklin et al, 2014) have reported that a context when the primary caregiver withdraws after interaction to not talking or interacting with the infant elicits high rates of vocalisations from infants at least 5 months of age. Note, however, that in these lines of research, interaction and effects of increased interaction or withdrawal from it have been the exclusive focus.…”
Section: Discussionmentioning
confidence: 99%
“…Goldstein, King, & West, 2003; Nathani & Stark, 1996). On the other hand, 5–6-month-olds’ volubility was found to substantially increase from a face-to-face episode to a still-face episode (Goldstein, Schwade, & Bornstein, 2009; Delgado, Messinger, & Yale, 2002; Franklin et al, 2014). In the still-face episode, the parent does not interact or respond with the infant but still looks directly at the infant.…”
Section: Introductionmentioning
confidence: 92%
“…Volubility is the quantity or rate of vocalization per unit time, and volubility matching quantifies the similarity between infant and adult volubility across a given recording session. Much work has demonstrated volubility to be an important predictor of vocal development and communication (Franklin et al., ; Gilkerson & Richards, ; Goldstein & West, ; Goldstein, Schwade, & Bornstein, ; Hart & Risley, ; Hsu, Fogel, & Messinger, ; Oller, Eilers, Basinger, Steffens, & Urbano, ; Rescorla & Ratner, ; Warlaumont et al., ), but less work has quantified its coordination across infant and caregiver pairings. In one study, Hart and Risley () found a positive relationship between infant and adult volubility.…”
Section: Goals Of the Current Studymentioning
confidence: 99%
“…Not only is the volubility of infants influenced by social context and past dyadic interactions with caregivers [5,6], but caregivers who preferentially and contingently respond to speech-like infant vocalizations spur the development of more complex vocalizations from those infants [7**,8**]. Conversely, parents are more likely to contingently respond to infant vocalizations if they sound more mature or speech-like [9].…”
Section: Introductionmentioning
confidence: 99%